LAYOUTS, PLANS, AND GASTRONOMY TRAVEL ROUTES IN SUDIRMAN BANDUNG CITY STREET - Kenny Stevan; Dewi Turgarini; Caria Ningsih (Kepariwisataan: Jurnal Ilmiah, 2022)
Sudirman Street is one of the Chinese culinary centers in the city of Bandung, not only as a center for Chinese cuisine, but also the legendary Chinese gastronomy around Sudirman Street. This study was made to determine the layout, floor plan, and route of Chinese gastronomy on Sudirman Street, Bandung City. This study uses descriptive qualitative research methods. The research subject is the Sudirman Street manager and stake holder with Miss Helix model of cinyusu salad. The results of this study are aspects of Sudirman Street layout such as capacity, cost, and a wide, easy and affordable process, then floor plans made by researchers for the efficiency of Halal and Non-Halal food, and the pattern of culinary travel routes on Sudirman Street, Bandung City.